The shape of things: magazine ads and the female body ideal - Christner, Rebecca (Kansas State University, 2008)
Recent research on magazine advertisements, for the most part, has examined race in terms of representation and gender in terms of stereotypical social roles and objectification. Very few content analyses have been done regarding the depictions of women in terms of specific body types portrayed in the advertising content of women's and teen magazines. In addition, very few, if any, studies have examined women's and teen's magazine advertisements for the presence of gender and racial stereotypes, overt sexuality, and depictions of a body ideal. This content analysis of six mainstream women's magazines explores the existence of all those variables and puts them in context with one another, examining the implications for what these advertisements say about our society. Specifically, this study focuses on the portrayals of women in women's and teen magazines, where previous studies have examined portrayals of women in general magazines or men's magazines, but no focus has been put on teen magazines or specifically women's magazines. Major findings include the obvious suggestions of specific body ideals for women and teens of different racial backgrounds, perpetuation of social role expectations and social stereotypes, and lack of sexual imagery prevalence in women's and teen magazines.
Keywords: Advertising; Women's magazines; Teen magazines; Body image; Stereotypes; Body ideal; Journalism (0391); Mass Communications (0708); Women's Studies (0453)